Predictors of parenting stress in parents of children with cancer. (October 2021) - Çınar, Sevil; Boztepe, Handan; Ay, Ayşe; Yılmaz, Pınar; Güllü, Hafize; Karadavut, Burcu; Burhanoğulları, Dilek; Solmaz, Murat; Akyüz, Canan
Abstract: Purpose: In the present study, we investigated the parenting stress experienced by parents of children with cancer and the influencing factors. Method: This was a cross-sectional and descriptive correlational study that consisted of parents of 136 children in the age group of 0–18 years who were followed up for cancer in the outpatient clinics and services of a university hospital in Turkey. Parenting Stress Index, Burden Interview, Multidimensional Scale of Perceived Social Support, Marital Life Satisfaction Scale, and Ways of Coping Questionnaire were used to collect the data. Results: No statistically significant difference was found between the parenting stress mean scores and gender of the parents of children with cancer ( t  = −0.350; P = 0.727). The results of the present study showed that the economic status ( t  = −4.16; P = 0.000), parents' physical ( t  = 3.606; P = 0.000) and mental health status after the child is diagnosed ( t  = 5.647; P = 0.000), accompanying mental health problems of the child ( t  = 2.567; P = 0.011), and diagnosis of children at a young age ( t  = −2.776; P = 0.006) increased the parenting stress of the parents. Conclusions: Nursing interventions can reduce parental stress by providing sufficient care and support during the disease process. Highlights: Financial status, parents' physical and mental health status increased the parenting stress of the parents. It is important to apply interventions that will reduce parental stress by providing sufficient care for the disease process. Healthcare professionals should be trained to understand factors affecting parenting stress.